Comportamiento de Calidris alba (Scolopacidae) en el Humedal Costero Poza de la Arenilla, la Punta, Callao, Perú - Podestá, Jorge; Franke, Irma; Barona, Daniel; Aponte, Héctor (Instituto de Ecología, A.C., 2022)
With the objective to evaluate the behavioral patterns of the sandpiper Calidris alba (Scolopacidae), observations were made between August and September 2019, in the Poza de la Arenilla Coastal Wetland (Callao, Peru). Each observation session lasted 600 seconds (10 min.), with a total observation time of 40,200 seconds, where was applied the "focal sampling" technique. Were identified 58 types of behavior grouped into eight categories. The four main behavior categories in relation to total observation time were: resting (37%), locomotion (26%), grooming (13%) and foraging (11%); other categories occupied 13%. In addition, in relation to the total observation time, he mainly performs four behaviors: resting with beak between the wings (15%), resting (13%), running (13%) and walking (9%). Knowledge of the behavior patterns of C. alba allows obtaining relevant information to continue contributing to the ethology of this species and recognize the activities that frequently realized in coastal wetlands, laying the foundations for future work related to the behavior of different species of shorebirds in conservation areas, places that receive hundreds of individuals of these and other species each year.